Abrasive leaders who changed: learning from their experience. Issue 7 (18th June 2021) - Tucker, Lori J.; Williams, Peter E.
Abstract : Purpose: The purpose of this paper is to understand the experience of three formerly abrasive leaders who improved their conduct and management strategies following a workplace intervention. Design/methodology/approach: Narrative inquiry, a personal and collaborative research method, revealed the experience of three leaders in their shift from destructive behaviors. Concepts from adult development, specifically Kegan's constructive-development theory (CDT) and Mezirow's transformative learning theory (TL), provided a lens to better understand the leaders' personal development. Findings: This study culminated with three co-composed narrative accounts and an analysis of narrative threads. The focus of this paper is the interpretive narrative thread analysis. The developmental experience of these three leaders included disruption, awakening and equipping. Research limitations/implications: This study included three leaders. The experience of these leaders may not be representative of other formerly abrasive leaders. Practical implications: This initial exploratory study contributes to CDT and TL by suggesting leader interpersonal development is an intensely emotional experience that transcends the mechanics of developmental stages. In practice, this study indicates abrasive leaders may improve their conduct and management strategies with organizational support, including supervisor intervention and specialized professionals. Originality/value: This paper offers insight for scholars and human resource (HR) professionals on the emotionally intense experiential journey of leaders who improved their interpersonal conduct. This study introduces concepts from CDT and TL into the study of workplace psychological aggression (WPA), and it expands the limited knowledge of how HR can support positive perpetrator change.